Use of herbal medicines in Hemorrhoidal Disease (Research, Society and Development, 2023)
The present study is a review of the literature on the use of herbal medicines in the treatment of Hemorrhoidal Disease (HD), a type of anorectal pathology, whose clinical picture includes bleeding when defecating, anal discomfort, itching, pain and anal protrusion. We sought to gather data from clinical trials, guidelines, experimental studies and systematic reviews in order to present herbal medicines that have demonstrated efficacy in the treatment of HD, given that their standard management has several side effects and complications. Among the herbal medicines evaluated (eg. Terminalia chebula Retz, Allium iranicum and Centella asiatica L.) they showed significant improvement, mainly in parameters such as: bleeding, decrease in inflammatory activity, and in the clinical and endoscopic patterns of the disease. Therefore, there is a great need to introduce them as an alternative or adjuvant therapy to conventional treatment, and encourage further research to explore their clinical efficacy, thus cooperating to improve the quality of life of affected individuals.